Features and processing in agreement - Mancini, Simona, 1978- (Cambridge Scholars Publishing, 2018)
How do we comprehend language? Does our brain differentiate among the different types of grammatical and conceptual information that each sentence we read and listen to contains? Are these mechanisms sensitive to cross-linguistic similarities and differences? To answer these questions, this book provides a comprehensive overview of existing experimental and theoretical studies on language processing. Special emphasis is given here to the analysis of basic building blocks of language - features - and to an approach that relies on the fruitful interaction among theoretical linguistics, psycholin.